The Role of Islamic Religion Teachers in Preventing Bullying in Primary Schools - Ningsih, Wirda (Yayasan Minang Darussalam, 2023)
This study aims to understand how Islamic religion teachers can prevent and address bullying in primary schools. Through descriptive qualitative desk research, this study found that Islamic religion teachers should integrate Islamic values in school culture, teach moral values through Islamic religious education, and encourage empathy and compassion among students. In addition, teachers should also promote effective communication and conflict resolution, be role models for students, contribute to the creation of a safe and inclusive environment, and collaborate with other stakeholders. By doing these things, Islamic religion teachers can create a respectful and inclusive school environment and prevent incidents of bullying. The level of success in preventing and intervening in bullying will largely depend on how Islamic teachers implement effective strategies and approaches. This research provides an important foundation for Islamic teachers in their role in helping to address bullying in primary schools.